NAKED NECK CHICKEN: HISTORY, CHARACTERISTIC, AND CONSERVATION - T., Kostaman (Majalah Ilmiah Peternakan, 2020)
Naked neck chicken is a native/local chicken of Indonesia is not well known in terms of information of the history, potential, and characteristics; so it has not been used optimally. The most striking feature of the naked neck chicken does not have feathers on the neck. To maintain, conservation methods that have been carried out by the Indonesian Research Institute for Animal Production (Balitnak) is to preserve a live animal, but with of limited facilities and infrastructure can not continue. The data of the performance of naked neck chickens of reared in Balitnak have been collected and tabulated. The alternative of conservation undertaken by Balitnak to maintain a naked neck chicken germplasm is in the form of primordial germ cells (PGCs) which are frozen at a temperature of -196 °C which when required can be transferred to the recipient embryo. Source PGCs which is collected from the blood and gonad embryonic. Based on its potential, naked neck chicken has good performance, so it can be used as a local chicken producing meat and eggs. This paper is expected to be useful as supporting data for the conservation and development of local chickens in Indonesia, especially naked neck chicken and local chicken of Indonesian of generally.